2013
DOI: 10.1111/evo.12236
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Effects of Key Innovations on the Diversification of Bromelioideae (Bromeliaceae)

Abstract: The evolution of key innovations, novel traits that promote diversification, is often seen as major driver for the unequal distribution of species richness within the tree of life. In this study, we aim to determine the factors underlying the extraordinary radiation of the subfamily Bromelioideae, one of the most diverse clades among the neotropical plant family Bromeliaceae.Based on an extended molecular phylogenetic data set, we examine the effect of two putative key innovations, that is, the Crassulacean ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
206
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(225 citation statements)
references
References 72 publications
12
206
2
5
Order By: Relevance
“…All the phylogenies that have included more than one species of Bromelia have indicated that the genus is monophyletic (e.g., Schulte & Zizka 2008;Sass & Spech 2010;Silvestro et al 2014;Evans et al 2015). However, the monophyly of Bromelia was not confirmed in the present analysis, because of the positioning of B. irwinii.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…All the phylogenies that have included more than one species of Bromelia have indicated that the genus is monophyletic (e.g., Schulte & Zizka 2008;Sass & Spech 2010;Silvestro et al 2014;Evans et al 2015). However, the monophyly of Bromelia was not confirmed in the present analysis, because of the positioning of B. irwinii.…”
Section: Discussioncontrasting
confidence: 60%
“…Nevertheless, these factors might have been strong forces driving the speciation and the evolutionary success of Bromelia in the Cerrado. Similarly, the repeated expansions and contractions of the Atlantic Rainforest and Cerrado during the Pleistocene (Pennington et al 2004;Antonelli et al 2009;Antonelli & Sanmartin 2011;Silvestro et al 2014) may have affected the occupation of Bromelia and its speciation in the Atlantic Rainforest (Bromelia antiacantha, B. unaensis and B. binotii). Probably it is also the key for the migration of members of Bromelioideae from arid environments to the evergreen forest, the present diversity center for this subfamily (Martinelli et al 2008;Forzza et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre as oito subfamílias reconhecidas atualmente (Givnish et al 2007(Givnish et al , 2011, Bromelioideae é aquela com maiores problemas de delimitação genérica e cujos conceitos taxonômicos são claramente divergentes entre os diferentes tratamentos (e.g., Baker 1889; Mez 1896Mez , 1934Smith & Downs 1979). A maioria das hipóteses filogenéticas propostas até o presente converge para o monofiletismo da subfamília e para o reconhecimento de um clado eu-bromelioide com a maioria dos gêneros (e.g., Schulte et al 2009;Sass & Specht 2010;Givnish et al 2011;Silvestro et al 2014;Evans et al 2015). O clado nidularióide, tem sido reconhecido em diferentes análises, porém ainda subamostrado e com relacionamentos inconclusivos (Schulte et al 2009;Evans et al 2015).…”
Section: Introductionunclassified
“…Examples of such studies have been conducted within the Bromelioideae and Solanaceae. In Bromelioideae CAM photosynthesis correlated to net speciation, while the tank habit correlates with extinction (Silvestro et al 2014). Within Solanaceae core group self-incompatibility seems to drive speciation (Goldberg et al 2010).…”
mentioning
confidence: 96%